Comparison of Dental Injury Rates in Perioperative Intubation and Suspension Laryngoscopy for Otolaryngology Procedures - Caleb P. Wilson BS; Erica Romano MD; Nilesh R. Vasan MD (OTO Open, 2021)
Objective Direct laryngoscopy is an essential skill during perioperative intubation and otolaryngology procedures. Dental injury is a common complication of direct laryngoscopy. However, the technique and tools used by anesthesiologists, nurse anesthetists, and others during perioperative intubation and by ear, nose, and throat surgeons for their procedures are different. The purpose of this review is to explore the literature for all studies detailing rates of dental injury in each of these settings and to compare them to see if the approaches have a significant difference in rate of dental injury. Data Sources PubMed. Review Methods A comprehensive search of PubMed was performed through February 2021 with search terms “dental” and “intubation” or “laryngoscopy.” PRISMA guidelines were followed. Studies documenting rates of dental injuries during intubation or during laryngologic procedures were included, and the 2 groups were compared. Results Twenty-three studies met inclusion criteria: 17 in the perioperative intubation group and 6 in the suspension laryngoscopy group. There was an increased incidence of dental injury in the perioperative intubation group (4.86%) as compared with the suspension laryngoscopy group (1.70%). Conclusions The difference in dental injury rate between the groups could be due to the differences in direct laryngoscopy technique or tools used, the presence vs absence of a dental guard, or a combination of these factors. More studies need to be performed to develop definitive and specific conclusions to recommend changes that prevent dental injury.